Penerapan Manajemen Risiko Berbasis ISO 31000 untuk Mitigasi Risiko Operasional, Keuangan, dan Strategis pada UMKM Konveksi: Studi Kasus pada Bardikar Store di Era Transformasi Digital - Najla Putri Pramesdianti; Fidelairna Daniswara; Liati Sinta; Syahira Rachmadina; Alfiana (Indo Publishing, 2025)
Bardikar Store is a Small and Medium Enterprise (SME) convection business that produces varsity jackets, T-shirts, daily service uniforms (PDH), and soccer jerseys, operating with a sales system per dozen. In its operations, Bardikar Store faces various risks that potentially hinder production flow and business stability, such as delays in material supply, demand fluctuations, and unstable cash flow. This research aims to analyze the application of the ISO 31000 risk management framework in identifying, analyzing, evaluating, and mitigating risks within the convection business. The research method uses a qualitative approach supported by semi-quantitative data through production process observation, interviews with owners and employees, and risk assessment using a probability-impact matrix. The results indicate three dominant risks: raw material delays (score 56), fluctuations in per-dozen orders (42), and slow cash flow(42). The implementation of ISO 31000 proved to enhance the effectiveness of risk mitigation through supplier diversification, a 20% inventory planning strategy, implementing a 30% down payment, and digital marketing strategies. This study concludes that the consistent use of ISO 31000 is capable of increasing the effectiveness of Bardikar Store's risk management and providing a strategic foundation for the sustainability of convection SMEs.